The Establishment and Development of Muftiates in Tsarist Russia - Alper Alp (Gazi Akademik Bakış)
In this paper, muftiates which was founded in Tsarist Russia, composed important part of policy of Russian government on Muslim people and Islam religion and lasted for a long time was analyzed. Factors which influenced foundation process of Orenburg Ecclesiastical Assembly, Crimean Muftiate, Southern Caucasia Sunnite and Shiite Muftiates, their duties and authorities were put forward. It was mentioned that religious organizations which have equal rights and authorities were not formed in regions where Muslim people were dominant in Russia. The difference between perspective of Tsardom government and Muslim people towards muftiates were determined, the reflection of this situation on relation between Empire and Muslim people was stated in the sense of policy.